Daten-Fairness in einer globalisierten Welt - Friedewald, Michael; Roßnagel, Alexander; Neuburger, Rahild; Bieker, Felix; Hornung, Gerrit (Privatheit und Selbstbestimmung in der digitalen Welt | Privacy and Self-Determination in the Digital World, 2023)
This anthology contains selected papers from the conference organised by 'Forum Privatheit' in 2022, analysing questions relating to privacy, data sharing and data fairness from different perspectives. The contributions focus on the protection of weak interests, questions of fair competition in the data economy with its strong power asymmetries and governance approaches to creating more fairness. Conceptual ideas, technical solutions and concrete use cases provide insights into this increasingly relevant topic. With contributions by Hartmut Aden | Jürgen Anke | Stefanie Astfalk, Lorenz Baum | Felix Bieker | Fabiola Böning | Paulina Bressel | Jeong-Eun Choi | Fabian Dantscher | Leyla Dewitz | Simon Engert | Michael Friedewald | Marie-Louise Gächter | Armin Gerl | Daniel Guagnin | Simon Hanisch | Björn Hanneke | Marit Hansen | Antonios Hazim | Gunnar Hempel | Maria Henkel | Mar Hicks | Timo Hoffmann | Gerrit Hornung | Dietmar Jakob | Paul C. Johannes | Sebastian J. Kasper | Wolfgang Kerber | Steven Kleemann | Marcel Kohpeiß | Jonathan Kropf | Uwe Laufs | Florian Müller | Maxi Nebel | Rahild Neuburger | Isabella Peters | Lars Pfeiffer | Alexander Roßnagel | Sascha Schiegg | Tom Schmidt | Sabrina Schönrock | Christian Schunck | Rachelle Sellung | Tahira Panahi | Louisa Specht-Riemenschneider | Martin Steinebach | Juliane Stiller | Thorsten Strufe | Milan Tahraoui | Julian Todt | Violeta Trkulja | Markus Uhlmann | Inna Vogel | Melanie Volkamer | Sebastian Wilhelm | Matthias Winterstetter.